Formulasi dan Evaluasi Sifat Fisik Lotion Ekstrak Etanol Daun Kemuning (Murraya paniculata (L) Jack) dan Daun Lidah Buaya (Aloe vera Linn) - Windah Anugrah Subaidah; Yohanes Juliantoni; Wahida Hajrin (Sasambo Journal of Pharmacy, 2020)
The ultraviolet radiation and skin water loss could damage the skin. Kemuning leaves (Murraya paniculata (L) Jack) as a source of anti-oxidants and Aloe vera leaves (Aloe vera Linn) can prevent this action. This study aims to formulate and evaluate lotion containing the Kemuning leaves and Aloe vera extract. The extract of Kemuning leaves was obtained by sonication using 70% ethanol solvent. Aloe vera juice was obtained by smoothing the aloe vera gel then filtered using clean gauze.  The kemuning leaves extract and aloe vera extract had formulated into lotion preparation. The physical properties of the lotion (homogeneity, type of emulsion, pH, spreadability, and adhesion) were determined. The organoleptic test showed that the color of the lotion was pale yellow with a smooth texture and had extract scent. The lotion was showed good homogeneity, spreadability 7.31 cm, pH 7, type oil in water and adhesion 45 seconds. The physical properties parameters of lotion preparations showed that the lotion preparations had fulfilled the requirements of good preparations.